Tacrolimus Reverses the Pemphigus Vulgaris Serum-Enhanced Expression of Desmoglein in HaCaT Cells - Zhimin, Xie; Xiangnong, Dai; Qiaolin, Pan; Qingqing, Li; Xingdong, Ye (Archives of Clinical and Biomedical Research, 2022)
Background: Pemphigus vulgaris (PV) is associated with autoantibodies against desmoglein (Dsg), including Dsg1 and Dsg3. However, the precise mechanism by which acantholysis occurs in response to PV-IgG and the effect of tacrolimus for PV remains unclear. Method: To co-culture human HaCaT keratinocytes with DMEM medium containing 5%PV-sera to establish a cell model of pemphigus that can determine the effect of PV-sera and tacrolimus on Dsg mRNA transcription and protein expression in HaCaT cells. Dsg protein expression in HaCaT cells was evaluated by Western blotting and Dsg mRNA transcription by real-time PCR (RT-PCR). The distribution of Dsg1 and Dsg3 in HaCaT cells was determined by indirect immunofluorescence (IIF). Results: The application of 5% PV serum resulted in an increase in the transcription and expression levels of Dsg1 and Dsg3, whereas tacrolimus suppressed Dsg1 and Dsg3 expression. Tacrolimus inhibited PV seruminduced disruption of cell-cell contacts. Tacrolimus also downregulated the expression of Dsg1and Dsg3 compared with the PV group. IIF revealed that the linear deposits of Dsg1 on the surface of HaCaT cells in the PVsera group disappeared and were replaced by granular and agglomerated fluorescent particles on the cell surface, whereas the Dsg3 linear deposits still existed, but this effect could be reversed by tacrolimus. Conclusion: The Dsg3 antibody disrupts desmosome junctions by inducing endocytosis, resulting in desmosomal dissociation. Tacrolimus could reverse PV serum-induced enhancement Dsg expression in HaCaT cells.